THE OFFENCES OF EXPLOITATION OF PROSTITUTION IN POLISH PENAL LAW - Mozgawa – Saj, Marta (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2021)
Purpose: analysis of the regulations describing criminal offences relating to the exploitation of prostitution provided for in Article 204 of the Polish Penal Code (inciting another person to prostitution and facilitating another person’s prostitution – Article 204 § 1, procuring – Article 204 § 2, aggravated type - Article 204 §3). Methods: the main method used in the study is dogmatic analysis. A synthetic analysis of the available statistical data was also carried out. Results: the interest protected under Article 204 § 1-2 is primarily morality and in the case of child prostitution (art. 204 § 3) mainly psychophysical development of the minor. Pursuant to Article 204 § 1 of Polish Penal Code (PC) penalises the conduct of the perpetrator who, in order to derive a material benefit, induces another person to practice prostitution or facilitates it. These offences are generally-defined perpetrator offences and are not characterized by its result; they may be committed only intentionally (with direct intent). Procuring (Article 204 § 2) is understood as earning material gains from prostitution practised by another person. This is an offence committed by multiple acts, since the verb "earning" indicates repetition in the behaviour of the perpetrator. It is a generally-defined perpetrator and deliberate offence that can be committed in both forms of intent. In the aggravated type (Article 204 § 3) the aggravating circumstance is the minor age of the prostitute against whom the offender commits inciting, facilitation or procuring. Offences under Article 204 PC relatively rarely occur in Polish realities, and cases of convictions under this provision are even rarer (in 2018 in Poland, a total of 140 people were finally sentenced under Article 204 (§ 1-3) PC in Poland). Discussion: the current wording of Article 204 PC appears to be correct and does not raise any fundamental doubts as to its interpretation. A small number of convictions under Article 204 PC raises the question about the real picture of both the phenomenon of prostitution in Poland and the actual number of behaviours related to its unlawful exploitation.